Expandable and sequential hierarchies older and younger adults’ time spent and errors made in expandable and sequential hierarchies - Kurniawan, Sri Hastuti; Zaphiris, Panayiotis; Ellis, R. Darin (My University, 2002)
The present study investigates traversal times and click errors differences when 24 older and 24 younger computer users traversed expandable and sequential online hierarchies. Two- way ANOVA analyses show that older participants were slower but did not make more errors than younger participants. Neither hierarchy was superior in traversal time but the expandable hierarchy resulted in fewer errors in reaching the target. The results suggested a speed-accuracy trade-off in older computer participants. Although older participants signifi- cantly rated their computer experience lower than younger participants, experience did not alter any significance. The results suggest that older adults remain at a disadvantage in either hierarchy.
Keywords: Age related differences; Health information; Hierarchy